2020
DOI: 10.1007/s42979-020-00163-6
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Method for Detecting Covered Face Scenarios in ATM Surveillance Camera

Abstract: Covering face with accessories such as mask, scarf and sunglass is a common criminal activity in automated teller machine (ATM) robbery. Therefore, detection of covered face using ATM surveillance camera can be an effective solution to reduce robbery or crime. This paper presents a novel method to detect covered face from ATM surveillance camera images. Specifically, three facial features, i.e., skin color, elliptical face shape and facial width-to-height ratio (fWHR), incorporated with geometrical property of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Sikandar et al [15] suggested a technique to detect masked faces from automated teller machine (ATM) monitoring security cameras correctly, and the detection rate was 96.48%. Rao et al [16] proposed CNN model for facial detection that had an accuracy of 91.21% while scanning the public without a facemask.…”
Section: Introductionmentioning
confidence: 99%
“…Sikandar et al [15] suggested a technique to detect masked faces from automated teller machine (ATM) monitoring security cameras correctly, and the detection rate was 96.48%. Rao et al [16] proposed CNN model for facial detection that had an accuracy of 91.21% while scanning the public without a facemask.…”
Section: Introductionmentioning
confidence: 99%
“…The person's movement inside the ATM with covered faces like a helmet and face mask affects surveillance. The detection of the covered faces inside the ATM helps in suspicious activity detection and enables security using the Noise error detection techniques (Sikandar, et al 2020). Suspicious activity detection with Convolutional Neural Networks (CNN) gives much better results (Parab, et al 2020).…”
Section: Introductionmentioning
confidence: 99%